Grammatical Type of Stepwise Transposition of Nominal Word Form ‘ryadom’ [near] into Subclass of Manner Adverbs - V. V. Shigurov; Т. A. Shigurova (Научный диалог, 2024)
The relevance of the study is determined by the necessity of a systematic   analysis of the linguistic mechanism of transposition, which produces a vast range of peripheral and hybrid formations in speech. The investigation of degrees of adverbial transposition of nouns has revealed certain regularities in the interaction of semantic and grammatical aspects within the structure of adverbialized word forms. Using the example of the word form ‘ryadom’ [near], different stages of adverbialization of instrumental case forms have been demonstrated, indicating the degree of deviation from nouns and convergence with adverbs. By employing the methodology of oppositional analysis (with a scale of transitivity) and indexing, it has been established that within the periphery of the adverbial class, there are proper grammatical (functional) adverbs that do not disrupt the semantic identity of the original lexemes and represent a distinct (adverbial) type of usage. The analysis of the syncretic structure of the peripheral adverb ‘ryadom’ [near] has shown that it exhibits 4% correspondence to the differential features of the core noun ‘ryadom’ (‘row’ in the instrumental case) and 64% correspondence to the differential features of the core adverb ‘ryadom’ [near]. These findings can be utilized in further exploration of intercategorical transposition and syncretism of linguistic units, as well as in the development of a transpositional grammar for the Russian.